BINGKAI REFORMASI BIROKRASI INDONESIA - Adam Idris (Jurnal Paradigma (JP), 2017)
Bureaucracy is a service provided by the government to the people. Up till now Society consider that the bureaucracy is a state instrument that needs to have its own rules and it is supported by its own laws, therefore the correlation between the bureaucracy and the executive should be arranged so the bureaucracy can do hardworking as a servant of the state and not as a man of power . Further, bureaucracy reformation needs to be implemented so that the bureaucracy is able to carry out their tasks more efficiently and effectively then a clean government and a good governance can be realized as well as the establishment of a good governance, clean and dignified governance.